2015
DOI: 10.1186/s40478-015-0199-x
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid accelerates tau propagation and toxicity in a model of early Alzheimer’s disease

Abstract: IntroductionIn early stages of Alzheimer’s disease (AD), neurofibrillary tangles (NFT) are largely restricted to the entorhinal cortex and medial temporal lobe. At later stages, when clinical symptoms generally occur, NFT involve widespread limbic and association cortices. At this point in the disease, amyloid plaques are also abundantly distributed in the cortex. This observation from human neuropathological studies led us to pose two alternative hypotheses: that amyloid in the cortex is permissive for the sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
171
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(197 citation statements)
references
References 29 publications
23
171
3
Order By: Relevance
“…Compact, congophilic Aβ deposits, induced or spontaneously formed in APP tg animals, are surrounded by degenerating neuritic boutons in which hyperphosphorylated tau has accumulated [76]. Human mutated APP and human mutated tau tg mice have been crossed to study the interaction of Aβ and tau pathologies [100]. Neurofibrillary tangles are initially found in the entorhinal cortex in tg mice expressing P301L human tau predominantly in that area (rTgTauEC) [135].…”
Section: In Animalsmentioning
confidence: 99%
“…Compact, congophilic Aβ deposits, induced or spontaneously formed in APP tg animals, are surrounded by degenerating neuritic boutons in which hyperphosphorylated tau has accumulated [76]. Human mutated APP and human mutated tau tg mice have been crossed to study the interaction of Aβ and tau pathologies [100]. Neurofibrillary tangles are initially found in the entorhinal cortex in tg mice expressing P301L human tau predominantly in that area (rTgTauEC) [135].…”
Section: In Animalsmentioning
confidence: 99%
“…The temporal dynamics of these neuropathologic processes may be one explanation for the close correlation between tau pathology and dementia severity, whereas A β shows no additive predictive value 2. Interestingly, animal studies – more appropriate to investigate the temporal relationship of protein accumulation than postmortem studies – recently suggested a synergistic effect of A β ‐mediated tau propagation and neuronal loss 3. However, the relative contributions of A β and tau pathology to AD‐related neurodegeneration in humans remain elusive.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the rTgTauEC/APP/PS1 mice also showed increased tau-induced neuronal loss [142]. There is still debate and discrepancy in the field as to the toxic species of tau, with oligomeric species emerging as an attractive candidate for both toxicity and seeding, although it should be noted they are not the only species to show efficacious seeding, but have been shown to be upregulated following transgenic lysate and EV injection in our studies [146,154].…”
Section: Discussionmentioning
confidence: 59%
“…Tat accelerated the speed and trajectory of tau spreading [142]. However, when isolating specific mechanisms involved in seeding it is preferable to begin to establish roles, such as those of extracellular vesicles, in simpler models first.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation